An assessment on the effects of 1-pentanol and 1-butanol as additives with Calophyllum Inophyllum biodiesel. (15th February 2018) - Nanthagopal, K.; Ashok, B.; Saravanan, B.; Patel, Deepam; Sudarshan, B.; Aaditya Ramasamy, R.
Highlights: Diesel engine is running successfully with higher alcohol fractions in the blend. Higher the alcohol fraction in the blend lower the brake thermal efficiency. Addition higher alcohol with biodiesel increases the HC, CO and smoke emissions. Oxides of nitrogen emission is lower for all alcohol-biodiesel blends. Significant reduction in cylinder pressure is noted for higher fraction of alcohol. Abstract: The aim of the present study is to investigate the effect of higher alcohols with Calophyllum Inophyllum biodiesel on the diesel engine characteristics under various engine loads. Two higher alcohols have been identified for the present investigation namely 1-pentanol and 1-butanol and the six fuel samples have been prepared with Calophyllum Inophyllum biodiesel at 40%, 50% and 60% concentrations by volume. All the experiments are carried out in a single cylinder, four stroke and constant speed diesel engine and the experimental results are compared with conventional diesel and pure biodiesel fuels. The study revealed that the diesel engine operation with higher alcohol-biodiesel blends has shown lower brake thermal efficiency and higher brake specific fuel consumption. The reduction rate is higher with a higher concentration of alcohol in the fuel blends. On the other hand, the cooling effect of higher alcohol in the blend reduces the NOx emission due to their higher latent heat of vaporization. Moreover, the CO, HC and smoke emissions are decreased for all higher alcohol-biodiesel blends. The combustion characteristics are followed similar pattern for all tested fuels and peak pressure is comparatively lower for higher concentration of alcohol in the fuel blend. Finally, it is revealed that 1-pentanol and 1-butanol can be successfully used as partial substitute to diesel or biodiesel fuel.